2020
DOI: 10.21203/rs.3.rs-93842/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Safety and Accuracy of Suction Rectal Biopsy in Preterm Infants

Abstract: Purpose: Little attention were paid in the diagnosis of preterm infants with Hirschsprung disease (HD) in most pediatric surgeons. We aimed to explore the safety and accuracy of suction rectal biopsy (SRB) in preterm infants.Methods: A retrospective review was conducted on 45 preterm patients who underwent SRB from 2015 to 2019 in our hospital. We collected the clinical characteristics and pathology results of the patients, and followed up. The sensitivity and specificity of SRB for HD diagnosis were calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…However, in our study, we did not observe a significant difference in the gross incidence of PVL or in subgroups between the early and late caffeine treatment groups. This finding is consistent with a retrospective study reported by Yang et al (18).…”
Section: Discussionsupporting
confidence: 94%
“…However, in our study, we did not observe a significant difference in the gross incidence of PVL or in subgroups between the early and late caffeine treatment groups. This finding is consistent with a retrospective study reported by Yang et al (18).…”
Section: Discussionsupporting
confidence: 94%